Structural equation model analysis of promoting physical activity behavior among college students: based on control-value theory of achievement emotions - Li, Han; Fang, Tao; Wu, Xinbo; Zhou, Zhenqian; Wu, Xilong; Zhang, Zhengxiao; Kim, Sukwon (Frontiers in Psychology, 2025)
BackgroundPrior studies have examined various determinants of college students’ physical activity behaviors; however, limited attention has been given to the role of a supportive environment within physical education courses. According to Pekrun’s control-value theory of achievement emotions, individuals’ appraisals of control and value in specific learning contexts evoke corresponding achievement emotions, which subsequently influence their learning behaviors and outcomes.ObjectiveThis study aimed to examine how a supportive teaching environment in physical education classes influences college students’ physical activity behaviors through control-value appraisals and achievement emotions, contributing to a broader application of the control-value theory of achievement emotions.MethodA total of 1,562 college students from five universities in China completed questionnaires, including the Physical Education Demand Support Questionnaire, Academic Control Scale, Subjective Task Value Scale of Sports, Achievement Emotions Questionnaire, and Physical Activity Rank Scale-3. Structural equation modeling (SEM) was used to validate the relationships.ResultsControl-value appraisals and two achievement emotions—enjoyment and boredom—played partial mediating roles in the relationship between a supportive teaching environment and college students’ physical activity behaviors. The chain indirect effects through control appraisal and enjoyment, and through control appraisal and boredom, were 0.022 and 0.008, respectively. Similarly, the indirect effects through value appraisal and enjoyment, and through value appraisal and boredom, were 0.034 and 0.010, respectively.ConclusionTeacher autonomy support indirectly influenced college students’ physical activity behaviors through control-value appraisals and achievement emotions, particularly enjoyment and boredom. Enjoyment emerged as an important achievement emotion that positively shaped exercise motivation and behavior, highlighting the critical role of emotional experiences in linking supportive teaching environments with students’ physical activity. These findings extend the control-value theory of achievement emotions to the context of physical education and provide empirical evidence for promoting teacher autonomy support to foster students’ exercise engagement.